Extragenital Gonorrhea and Chlamydia Testing Among Women Reporting Extragenital Exposure at an Urban STD Clinic: Is It Worth the Cost? - Caragol, Laura (Open Forum Infect Dis, 2017)
BACKGROUND: Current guidelines only recommend screening for gonorrhea (GC) and chlamydia (CT) at extragenital sites of exposure in men who have sex with men (MSM). With Medicaid reimbursement for GC/CT nucleic acid amplification testing (NAAT) at approximately $48/test, expanding testing to women requires a value assessment. We report the prevalence of extragenital GC/CT in women with extragenital exposure, determine the proportion of disease missed by urogenital NAAT, and estimate additional cost per infection identified by extragenital testing in women vs MSM. METHODS: We conducted a retrospective analysis of women undergoing extragenital NAAT for GC and CT at Denver Metro Health Clinic. Data were analyzed for all women with extragenital testing from 9/11/2015 to 7/8/2016, and for MSM from 9/3/2013 to 7/8/2016. Statistical Package for the Social Sciences and Excel programs were used for data analysis. RESULTS: In a total 804 female visits, the mean age was 29 (13–67years); 46% were White non-Hispanic; 37% were Hispanic; and 15% were Black. In women, the prevalence of extragenital GC and CT was 2% (16/804) and 5% (38/804), respectively. The rate of GC infection in women was the same at genital and pharyngeal sites (2%, 16/804) but lower at the rectum (0.25%, 2/804). Female chlamydia rates were 11% genital (85/804), 4% pharyngeal (30/804), and 1.4% rectal (11/804). If only urogenital testing had been performed in women, 27% (6/22) of GC infections and 14% (14/99) of CT infections would have been missed. Overall, isolated extragenital infection accounted for 18% (20/111, 95% CI 12–26%) and 65% (943/1453, 95% CI 62–67%) of the combined GC and CT burden in women and MSM, respectively. On average, 40 women and five MSM were screened with extragenital tests to identify one isolated extragenital infection. Estimated additional Medicaid costs for isolated extragenital infection identified in women was $3,851 and in men was $480 for pharyngeal and rectal testing. CONCLUSION: Urogenital screening misses a significant number of extragenital infections in women. However, given the high cost of extragenital screening in women, further work is needed to determine whether screening can be limited to the pharynx or if risk factors can be used to target screening for cost savings. DISCLOSURES: All authors: No reported disclosures.